The high school academy as a laboratory of equity, inclusion, and safety. Issue 4 (2nd October 2019) - Fletcher, Edward C.; Warren, Nathalie Q.; Hernandez-Gantes, Victor M.
ABSTRACT: Background and Context: Career academies emphasize learning in specific occupational contexts to enhance the relevance of student experiences. The premise is that the authenticity of occupational contexts provides for opportunities to make learning more meaningful for students. Objective: The purpose of this case study was to examine the school culture of an IT academy. Method: We followed a qualitative, case study design. Findings: We found the academy had a positive school culture, embraced a unique attitude of acceptance for others, and was a safe place for students. The elements of the academy that were associated with a positive school culture included the open enrollment policy, wall-to-wall nature, small size, and student shared interests by focusing on IT as a curricular theme. Implications: Findings of this study highlighted effective approaches (i.e. open enrollment policy, wall-to-wall IT nature, and small size) high school administrators can utilize to develop a positive school culture.